Bridging planets and stars using scaling laws in anelastic spherical shell dynamos. Issue Volume 9:Issue S302(2013) (7th August 2014) - Yadav, R. K.; Gastine, T.; Christensen, U. R.; Duarte, L.
Abstract: Dynamos operating in the interiors of rapidly rotating planets and low-mass stars might belong to a similar category where rotation plays a vital role. We quantify this similarity using scaling laws. We analyse direct numerical simulations of Boussinesq and anelastic spherical shell dynamos. These dynamos represent simplified models which span from Earth-like planets to rapidly rotating low-mass stars. We find that magnetic field and velocity in these dynamos are related to the available buoyancy power via a simple power law which holds over wide variety of control parameters.